Jackpot [compact disc, unabridged] - Woods, Stuart; Quertermous, Bryon (A Teddy Fay novel, 2021)
When Peter Barrington and Ben Bachetti come under threat while working at a film festival abroad, Teddy Fay is lured to the glittering city of Macau to resolve the problem.